IL-2 Inhibition of Th17 Generation Rather Than Induction of Treg Cells Is Impaired in Primary Sjögren’s Syndrome Patients - Luo, Jing; Ming, Bingxia; Zhang, Cai; Deng, Xiaofei; Li, Pingfei; Wei, Zhengping; Xia, Yu; Jiang, Kan; Ye, Hong; Ma, Wanli; Liu, Zheng; Li, Huabin; et al. (Frontiers in Immunology, 2018)
Objective：To investigate the role of IL-2 in the balance of Th17 and Tregs and elucidate the underlying mechanisms of enhanced Th17 differentiation in primary Sjögren's Syndrome (pSS) patients. Methods：This study involved 31 pSS patients, 7 Sicca patients and 31 healthy subjects. Th17 and Treg cells were determined by flow cytometry and immunohistochemistry. IL-2 and IL-6 levels were assessed by ELISA and qPCR. p-STAT5 and p-STAT3 in salivary glands (SG) were evaluated by immunohistochemistry. The binding of STAT5 and STAT3 to the Il17a gene locus was measured by chromatin-immunoprecipitation. Results：We found that the percentage of Th17 cells was increased in the periphery and SG of pSS patients compared with healthy subjects, but the Treg cells was unchanged. Meanwhile, IL-2 level was reduced and the IL-6 level was increased in the plasma of pSS patients. The ratio of IL-2 and IL-6 level was also decreased. The expression of Il6 and Il17a mRNA was significantly increased, whereas Foxp3, Tgfb1, Tnfa and Ifng mRNA were comparable. Furthermore, the level of STAT5 phosphorylation (p-STAT5) was reduced and p-STAT3 was enhanced in the SG. In vitro IL-2 treatment-induced p-STAT5 increased and competed with STAT3 binding in human Il17a locus, leading to decreased Th17 differentiation, which was associated with the reduced transcription activation marker H3K4me3. Conclusions：Our findings demonstrated a Treg-independent up-regulation of Th17 generation in pSS, which is likely due to a lack of IL-2-mediated suppression of Th17 differentiation. This study identified a novel mechanism of IL-2-mediated immune suppression in pSS. Key Words: Sjögren syndrome, IL-2, Treg, Th17, p-STAT5